Relationship of serum 25-hydroxyvitamin D [25(OH)D] concentration with diabetic patients attending BIRDEM Hospital, Dhaka (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Epidemiologic studies have shown that low vitamin D levels are associated with reduced insulin sensitivity and increased risk of developing type 2 diabetes mellitus. Many studies have been reported that serum concentration of vitamin D are lower in type 2 diabetic patient and non diabetic patient also in relation to age, sex, occupation, dietary intake and sun exposure. Objectives: The present study was aimed to assess the serum 25-hydroxyvitamin D concentration [25(OH)D] among adult population attending BIRDEM hospital with and without type 2 diabetes mellitus and also find out the relationship between the deficiency of vitamin D and development of type 2 diabetes mellitus.Materials and Methods: It was an analytical cross sectional study where around 250 subjects were taken purposively and among them, 200 were type 2 diabetic subjects and 50 were non diabetic. Study was conducted at BIRDEM hospital within the age group 18 to 65 years from January 2015 to December 2015. Data about socio-demographics were collected, blood pressure, height, weight were measured and BMI were calculated. Glycaemic status was assessed by HbA1c% and plasma glucose level. Vitamin D was measured by HPLC and SPSS (17) was used for t-test, chi-square test, ANOVA & Pearson's correlation coefficient test. Anthropometric and Biochemical parameters were collected by pre-questionnaire from the record book of the patient.Results: The percentage of low serum 25-hydroxyvitamin D concentration [25(OH)D] was significantly higher in type 2 diabetics than non diabetics, that was 55.5% vs 20% (p value